Técnicas grafoplásticas como herramienta de desarrollo psicomotriz fino, en niños de 2 a 3 años del Cdi “Mi Angelito Corre” de la provincia los Rios, cantón Babahoyo, recinto la Angela. - Jiménez Guerra, Silvana Leonela (2019)
The objective of the research was to determine how graphoplastic techniques help in the fine psychomotor development in children from 2 to 3 years of the CDI "Mi Angelito Corre" of the Province of Los Ríos, Cantón Babahoyo, Recinto la Ángela. The established methodology presents a mixed approach, that is, quali - quantitative, and is based on a descriptive scope. The study population was 24 children (4 educator, 9 children and 11 girls) between the ages of 2 and 3years, belonging to the grade school "Initial Education". In addition, a stimulation plan was applied based on graphoplastic techniques for the fine psychomotor development of children from one to three years old. The t-student test statistic was used, and it was corroborated that the P value is less than 0.05. In this way, the hypothesis of discussion is ratified; the graphoplastic techniques DO have a significant impact on the fine psychomotor development of the children of the Integral Development Center. The main results reflect that, 95% of children present deficiency in psychomotor skills, in the same way, in the second data collection, 90% of children, require surveillance in their activities, and have overcome that negative barrier for their age. On the other hand, the remaining 10% maintain normal psychomotor skills. In conclusion, special emphasis should be placed on the study group, since it is very likely that they will encounter a series of subsequent problems. Keywords: Graphoplastic techniques, Infant education, Psychomotor development, Plastic expression.